Military Police Jurisdiction in Investigating Connectivity-Related Criminal Cases - Arief Fahmi Lubis (Jurnal Media Administrasi, 2020)
The investigation of connectivity-related cases is conducted by a dedicated team composed of Military Police officers and prosecutors, each acting within their respective legal jurisdictions for criminal investigations. This study aimed to demonstrate that the Military Police, in conjunction with other law enforcement agencies within the Indonesian National Armed Forces (Indonesian: Tentara Nasional Indonesia [TNI]), must collaborate to assist TNI leadership in upholding discipline and fostering awareness of legal compliance among TNI personnel. This collaboration is essential for creating highly disciplined and professional TNI personnel in carrying out their duties and maintaining order and discipline within the units. This study was qualitative research, employing a descriptive approach to systematically gather factual and timely data aligned with the research objectives. The findings revealed that the resolution of connectivity-related cases may be adjudicated in either civilian or military courts, depending on the severity of the harm. To coordinate the handling of such cases in civilian or military courts, the Deputy Attorney General for Military Criminal Affairs (Indonesian: Jaksa Agung Muda Bidang Pidana Militer [JAMPIDMIL]) has been established.